2007
DOI: 10.1002/joc.1500
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate variability on Alpine glaciers in northwestern Italy

Abstract: Abstract:We analyzed glacier snout fluctuation data in Piedmont and Val d'Aosta (Italy) and studied the impact of climate variability on valley glaciers in the western Italian Alps. The study period covered about 70 years in the 20th century; we focused on the last 50 years where a large number of temperature and precipitation time series are available. Superposed onto a general recession trend, we detected strong oscillations on shorter time scales and we showed that they are significantly correlated with fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The study of some of these impacts has been reported elsewhere (Jacobson et al, 2004) and a general study of the response of glaciers in the western Alps to climate change has been recently completed (Calmanti et al, 2007).…”
Section: Tablementioning
confidence: 99%
“…The study of some of these impacts has been reported elsewhere (Jacobson et al, 2004) and a general study of the response of glaciers in the western Alps to climate change has been recently completed (Calmanti et al, 2007).…”
Section: Tablementioning
confidence: 99%
“…Italian glaciers are located on the Southern flank of the Alps, mainly in the Western and Central Alps, and the Italian Alps tend to have far fewer and smaller glaciers than the Northern and North-Western sides, due to exposure. Moreover, most Italian glaciers are situated at high elevations, but other factors, such as local climatic conditions (Faletto, Prola, Acquaotta, Fratianni, & Terzago, 2013), related to the source and propagation of humid maritime air, also influence their size and distribution (Calmanti, Motta, Turco, & Provenzale, 2007).…”
Section: Geomorphological Settingmentioning
confidence: 99%
“…Such morphological changes are of interest predominantly because they are symptomatic of a warming climate, indicating changes in local to regional scale temperature and precipitation gradients (Barry, 2006;Calmanti et al, 2007), but also because they can often provide an interesting insight into ablation mechanisms at a local scale, either through field observation or, where appropriate data are available, remote-sensing analyses. Understanding ablation mechanisms is, in turn, required for accurate modelling of energy balances and the future response of geomorphic and hydrological systems to continued climatic forcing (Kirkbride, 1995a).…”
Section: Introductionmentioning
confidence: 99%